Preparation method of Ni electrode strontium titanate annular piezoresistor
By using Ni pulp and composite nanomaterials, the problem of unstable resistance value of titanate cycle -shaped voltage resistors under high -pressure and high temperature conditions is solved, and better adhesion and stability have been achieved, reducing production costs.
Patent Information
- Application Number
- CN202411521884.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-29
AI Technical Summary
After the existing strontium titanate annular varistors are subjected to pulse voltage or thermal shock of solder, the varistor value drops significantly, resulting in unstable resistance value.
Ni paste is used to replace ohm silver pulp as a slurry that forms ohm, and introduces composite nanomaterials in nickel mining. It forms a stable ceramic substrate and nickel silver layer by sintering and oxide heat treatment.
Improve the adhesion and stability between the nickel and ceramic substrates, reduce the production cost, and enhance the structural stability of the resistor, and avoid the decline in the resistance value.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of annular varistor preparation, in particular to a method for preparing a Ni electrode strontium titanate annular varistor. Background Art
[0002] Strontium titanate ring varistor is an electronic component used in micro DC motors to absorb sparks, suppress surges and eliminate noise.
[0003] In the existing process of strontium titanate ring varistor, silver is mainly used as the electrode. The manufacturing process of this varistor is: first use silk screen to print the first layer of ohmic silver paste and dry it at a temperature of 100℃-200℃; then use silk screen to print the second layer of silver paste and dry it at a temperature of 100℃-200℃; finally, the two layers of silver paste are sintered at a temperature of 580℃-680℃ for silver reduction. The reason for printing silver paste twice is that silver paste is a paste that does not have ohmic characteristics. There is an oxygen barrier between the silver layer of the varistor printed with only silver paste and the porcelain body. After a certain degree of pulse voltage shock or solder heat shock, the varistor voltage will drop significantly, which is reflected in the significant drop in resistance value. Therefore, before printing silver paste, it is necessary to print a layer of paste with ohmic contact (Ag-Zn); and this ohmic paste itself has almost no solderability, so it is necessary to print another layer of solderable silver paste.
[0004] In view of this, it is indeed necessary to provide a new type of annular varistor, which uses Ni paste instead of ohmic silver paste (Ag-Zn) as the paste for forming ohmic contact and has good adhesion and stability. Summary of the invention
[0005] In view of the problems existing in the prior art, the object of the present invention is to provide a method for preparing a Ni electrode strontium titanate ring varistor.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The preparation method of Ni electrode strontium titanate ring varistor specifically comprises the following steps:
[0008] 1) using a servo molding machine to dry-press strontium titanate powder into strontium titanate annular varistor green ceramic sheets;
[0009] 2) debinding and pre-firing the green ceramic sheet from step 1) at 1000-1200° C.;
[0010] 3) sintering the green ceramic sheet pre-fired in step 2) in a reducing atmosphere of a mixed gas composed of equal volumes of nitrogen and hydrogen to form a ceramic substrate;
[0011] 4) subjecting the ceramic substrate of step 3) to an oxidation heat treatment at 800-1000° C. to form an oxide film on the surface;
[0012] 5) The ceramic sheet of step 4) is screen-printed with a first layer of nickel paste and dried at a temperature of 100-200° C., and then a second layer of silver paste is screen-printed and dried at a temperature of 100-200° C., and then fired in an air atmosphere of 600-800° C.
[0013] As a further preferred embodiment of the present invention, the nickel paste is made of the following raw materials in parts by weight: 70-95 parts of nickel powder, 5-30 parts of powder, 8-13 parts of organic carrier, and 2-6 parts of composite nanomaterial;
[0014] The nickel slurry is prepared by preheating the ingredients of the organic carrier in a water bath at 90-93° C. to form a uniform solution, adding nickel powder, powder and composite nanomaterials into the organic carrier and stirring, then grinding with a three-roll grinder until the slurry has a particle size of less than 10 μm, and then filtering with a 300-mesh nylon net.
[0015] As a further preferred embodiment of the present invention, the powder material includes one or more of glass powder, silicate, silicon dioxide, boron trioxide, bismuth trioxide, and boron powder;
[0016] The organic carrier is composed of ethyl cellulose, pinene alcohol, dibutyl phthalate and oleic acid mixed in a mass ratio of (10-18): (30-50): (38-42): (0.5-1.2).
[0017] As a further preferred embodiment of the present invention, the preparation method of the composite nanomaterial is as follows:
[0018] 1) The porous nanomaterial is ultrasonically cleaned with acetone, distilled water and ethanol for 30-50 minutes respectively, and then dried to obtain a pretreated porous nanomaterial;
[0019] 2) dissolving cobalt nitrate hexahydrate in the mixed solution, stirring thoroughly, adding the pretreated porous nanomaterial therein, and then placing them together in a reaction kettle, reacting at 120-126° C. for 5-10 hours, cooling to room temperature after the reaction is completed, rinsing, drying, and then drying for standby use;
[0020] 3) placing the above-mentioned spare product in a tubular furnace, heating it to 700-750° C. in a nitrogen atmosphere, and keeping it warm for 90-120 min. After cooling to room temperature, reacting the obtained product with a sufficient amount of thioacetamide at 100-110° C. for 3-5 h. After cooling, washing and drying, a composite nanomaterial can be obtained.
[0021] As a further preferred embodiment of the present invention, the usage ratio of the cobalt nitrate hexahydrate, the mixed solution, and the pretreated porous nanomaterial is (3-7) g: (120-180) mL: (5-13) g;
[0022] The mixed solution is composed of N,N-dimethylformamide and methanol in a volume ratio of 1:(2-3).
[0023] As a further preferred embodiment of the present invention, the heating rate is 5-7°C / min.
[0024] As a further preferred embodiment of the present invention, the preparation method of the porous nanomaterial is as follows:
[0025] 1) dissolving nickel nitrate in deionized water, adding sodium oxalate and hexamethylenetetramine, reacting at room temperature for 4-6 hours, centrifuging, repeatedly washing with ethanol and deionized water, and drying to obtain a nanorod precursor;
[0026] 2) placing the nanorod precursor in a tube furnace, introducing nitrogen, heating to 350-380°C, and maintaining for 4-6 hours, after naturally cooling to room temperature, placing the obtained product and sodium hypophosphite in a mass ratio of 1:(10-13) in a tube furnace, heating to 300-320°C, and maintaining for 2-3 hours, after naturally cooling to room temperature, taking out, washing by centrifugation, and drying to obtain porous nanorods;
[0027] 3) Dispersing titanium dioxide nanowires in deionized water to obtain a dispersion, then placing the porous nanorods in a vacuum impregnation container, evacuating to 50-80 Pa, and then injecting the dispersion into a vacuum impregnation tank at a solid-liquid ratio of 1 g: (10-20) mL, and maintaining it for 30-50 minutes under ultrasonic treatment. After the treatment is completed, the product is taken out, centrifuged, washed and dried to obtain a porous nanomaterial.
[0028] As a further preferred embodiment of the present invention, the usage ratio of the nickel nitrate, deionized water, sodium oxalate and hexamethylenetetramine is (2-5) g: (260-400) mL: (1.3-1.8) g: (1.4-2.0) g.
[0029] As a further preferred embodiment of the present invention, the heating rate is 1-3°C / min.
[0030] As a further preferred embodiment of the present invention, the solid content of the dispersion is 1-3wt%;
[0031] The power of the ultrasonic action is 150-200W.
[0032] The beneficial effects of the present invention are:
[0033] In the present invention, a rod-shaped nanorod precursor is first synthesized by a room temperature precipitation method, and then calcined in a nitrogen atmosphere, and then phosphating is used to prepare a porous nanorod assembled from nanoparticles to form a porous rod. The surface of the porous nanorod has a rich pore structure and a rough surface structure. The porous nanorod and the titanium dioxide nanowire are physically structured by a vacuum impregnation method. Under the action of ultrasound, the titanium dioxide nanowire will be embedded in the pores of the porous nanorod, so that the two are connected together. Moreover, since the surface of the titanium dioxide nanowire is relatively smooth, some of the nanowires will become loose after being entangled with each other under the action of ultrasound. Therefore, after being subjected to ultrasound, the porous nanorod will be easily oxidized. After vacuum impregnation under the action of sound, a connection between the titanium dioxide nanowire and the porous nanorod is formed, thereby obtaining a porous nanomaterial; at the same time, in order to improve the bonding strength between the wire and the rod, in the present invention, the porous nanomaterial is repeatedly washed and then dried, and a hydrothermal method and a high-temperature roasting method are used to precipitate nanosheets on the surface of the porous nanomaterial. The deposited nanosheets can, on the one hand, cover and fill the connection between the wire and the rod, play a reinforcing role, and enhance the connection strength between the two. At the same time, the nanosheets are deposited on the surface of the nanowire, which increases the surface roughness of the nanowire, so that the contact area between the nanowire and the substrate is larger, making the bonding stronger.
[0034] In the present invention, Ni paste is used to replace ohmic silver paste as the paste for forming ohmic contact, and sintering is performed in the air. The cost is greatly reduced compared with ohmic silver paste, so that the subsequent production cost is low; at the same time, by introducing a composite nano material into the nickel paste, the end of the composite nano material presents a rod-shaped structure, the surface area is large, and there is a larger contact area with the nickel paste, so that the movement friction between the two is large, so the composite nano material can be better embedded in the nickel paste, and it is not easy to migrate, so that it can be stably embedded in the nickel paste, and because the front end of the composite nano material presents a linear structure, it is easy to be exposed from the nickel paste, and the surface is rough, there is a larger contact area with the ceramic substrate, so that it can better contact with the substrate and form a firm bond, so that the nickel paste has better adhesion on the ceramic substrate, good stability, and is not easy to delaminate. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the embodiment of the present invention, the powder is glass powder; the organic carrier is composed of ethyl cellulose, terpineol, dibutyl phthalate, and oleic acid mixed in a mass ratio of 13:42:40:0.9.
[0037] Example 1
[0038] The preparation method of Ni electrode strontium titanate ring varistor specifically comprises the following steps:
[0039] 1) using a servo molding machine to dry-press strontium titanate powder into strontium titanate annular varistor green ceramic sheets;
[0040] 2) debinding and pre-firing the green ceramic sheet of step 1) at 1000° C.;
[0041] 3) sintering the green ceramic sheet pre-fired in step 2) in a reducing atmosphere of a mixed gas composed of equal volumes of nitrogen and hydrogen to form a ceramic substrate;
[0042] 4) subjecting the ceramic substrate of step 3) to an oxidation heat treatment at 800° C. to form an oxide film on the surface;
[0043] 5) The ceramic sheet of step 4) is screen-printed with a first layer of nickel paste and dried at a temperature of 100° C., and then a second layer of silver paste is screen-printed and dried at a temperature of 100° C., and then fired in an air atmosphere at 600° C.;
[0044] The nickel paste is made of the following raw materials in parts by weight: 70 parts of nickel powder, 5 parts of powder, 8 parts of organic carrier, and 2 parts of composite nanomaterial;
[0045] The preparation method of nickel slurry is as follows: preheat the ingredients of the organic carrier in a water bath at 90°C to dissolve the ethyl cellulose into a uniform solution, then add nickel powder, powder and composite nanomaterials into the organic carrier and stir, then grind with a three-roll grinder until the slurry particle size is less than 10μm, and then filter through a 300-mesh nylon mesh.
[0046] The preparation method of the composite nanomaterial is as follows:
[0047] 1) Dissolve 2 g of nickel nitrate in 260 mL of deionized water, add 1.3 g of sodium oxalate and 1.4 g of hexamethylenetetramine, react at room temperature for 4 h, centrifuge, repeatedly wash with ethanol and deionized water, and dry to obtain a nanorod precursor;
[0048] 2) placing the nanorod precursor in a tube furnace, introducing nitrogen, heating to 350°C at 1°C / min, and maintaining for 4 hours, after naturally cooling to room temperature, placing the obtained product and sodium hypophosphite in a mass ratio of 1:10 in a tube furnace, heating to 300°C at 1°C / min, and maintaining for 2 hours, after naturally cooling to room temperature, taking out, washing by centrifugation, and drying to obtain porous nanorods;
[0049] 3) dispersing titanium dioxide nanowires in deionized water to obtain a dispersion with a solid content of 1 wt%, then placing the porous nanorods in a vacuum impregnation container, evacuating to 50 Pa, and then injecting the dispersion into a vacuum impregnation tank at a solid-liquid ratio of 1 g: 10 mL, and maintaining it for 30 minutes under 150 W ultrasonic action. After the treatment is completed, the product is taken out, centrifuged, washed and dried to obtain a porous nanomaterial;
[0050] 4) The porous nanomaterial is ultrasonically cleaned for 30 minutes using acetone, distilled water and ethanol respectively, and then dried to obtain a pretreated porous nanomaterial;
[0051] 5) Dissolve 3 g of cobalt nitrate hexahydrate in 120 mL of a mixed solution of N,N-dimethylformamide and methanol in a volume ratio of 1:2, stir thoroughly, add 5 g of the pretreated porous nanomaterial, and then put them into a reactor together, react at 120° C. for 5 h, cool to room temperature after the reaction is completed, rinse, dry, and then bake for later use;
[0052] 6) The above-mentioned spare product is placed in a tubular furnace, and the temperature is raised to 700°C at 5°C / min in a nitrogen atmosphere, and kept warm for 90 minutes. After cooling to room temperature, the obtained product is reacted with 0.13 mol of thioacetamide at 100°C for 3 hours. After cooling, washing and drying, a composite nanomaterial can be obtained.
[0053] Example 2
[0054] The preparation method of Ni electrode strontium titanate ring varistor specifically comprises the following steps:
[0055] 1) using a servo molding machine to dry-press strontium titanate powder into strontium titanate annular varistor green ceramic sheets;
[0056] 2) debinding and pre-firing the green ceramic sheet of step 1) at 1100° C.;
[0057] 3) sintering the green ceramic sheet pre-fired in step 2) in a reducing atmosphere of a mixed gas composed of equal volumes of nitrogen and hydrogen to form a ceramic substrate;
[0058] 4) subjecting the ceramic substrate of step 3) to an oxidation heat treatment at 900° C. to form an oxide film on the surface;
[0059] 5) The ceramic sheet of step 4) is screen-printed with a first layer of nickel paste, and dried at a temperature of 150° C., and then screen-printed with a second layer of silver paste, and dried at a temperature of 150° C., and fired in an air atmosphere at 700° C.;
[0060] The nickel paste is made of the following raw materials in parts by weight: 85 parts of nickel powder, 20 parts of powder, 10 parts of organic carrier, and 5 parts of composite nanomaterial;
[0061] The preparation method of nickel slurry is as follows: preheat the ingredients of the organic carrier in a water bath at 92°C to dissolve the ethyl cellulose into a uniform solution, then add nickel powder, powder and composite nanomaterials into the organic carrier and stir, then grind with a three-roll grinder until the slurry particle size is less than 10μm, and then filter through a 300-mesh nylon mesh.
[0062] The preparation method of the composite nanomaterial is as follows:
[0063] 1) Dissolve 3 g of nickel nitrate in 350 mL of deionized water, add 1.5 g of sodium oxalate and 1.8 g of hexamethylenetetramine, react at room temperature for 5 h, centrifuge, wash repeatedly with ethanol and deionized water, and dry to obtain a nanorod precursor;
[0064] 2) placing the nanorod precursor in a tube furnace, introducing nitrogen, heating to 365°C at 2°C / min, and maintaining for 5 hours, after naturally cooling to room temperature, placing the obtained product and sodium hypophosphite in a mass ratio of 1:12 in a tube furnace, heating to 310°C at 2°C / min, and maintaining for 2.5 hours, after naturally cooling to room temperature, taking out, washing by centrifugation, and drying to obtain porous nanorods;
[0065] 3) dispersing titanium dioxide nanowires in deionized water to obtain a dispersion with a solid content of 2 wt%, then placing the porous nanorods in a vacuum impregnation container, evacuating to 70 Pa, and then injecting the dispersion into a vacuum impregnation tank at a solid-liquid ratio of 1 g:15 mL, and maintaining it for 40 minutes under 180 W ultrasonic action. After the treatment is completed, the product is taken out, centrifuged, washed and dried to obtain a porous nanomaterial;
[0066] 4) The porous nanomaterial is ultrasonically cleaned for 40 minutes using acetone, distilled water and ethanol respectively, and then dried to obtain a pretreated porous nanomaterial;
[0067] 5) Dissolve 5 g of cobalt nitrate hexahydrate in 160 mL of a mixed solution of N,N-dimethylformamide and methanol in a volume ratio of 1:2.5, stir thoroughly, add 9 g of the pretreated porous nanomaterial, and then put them into a reactor together, react at 125° C. for 7 h, cool to room temperature after the reaction is completed, rinse, dry, and then bake for later use;
[0068] 6) The above-mentioned spare product is placed in a tubular furnace, and the temperature is raised to 720°C at 6°C / min in a nitrogen atmosphere, and kept warm for 100 minutes. After cooling to room temperature, the obtained product is reacted with 0.15 mol of thioacetamide at 105°C for 4 hours. After cooling, washing and drying, a composite nanomaterial can be obtained.
[0069] Example 3
[0070] The preparation method of Ni electrode strontium titanate ring varistor specifically comprises the following steps:
[0071] 1) using a servo molding machine to dry-press strontium titanate powder into strontium titanate annular varistor green ceramic sheets;
[0072] 2) debinding and pre-firing the green ceramic sheet of step 1) at 1200° C.;
[0073] 3) sintering the green ceramic sheet pre-fired in step 2) in a reducing atmosphere of a mixed gas composed of equal volumes of nitrogen and hydrogen to form a ceramic substrate;
[0074] 4) subjecting the ceramic substrate of step 3) to an oxidation heat treatment at 1000° C. to form an oxide film on the surface;
[0075] 5) The ceramic sheet of step 4) is screen-printed with a first layer of nickel paste and dried at a temperature of 200° C., and then a second layer of silver paste is screen-printed and dried at a temperature of 200° C., and then fired in an air atmosphere at 800° C.;
[0076] The nickel paste is made of the following raw materials in parts by weight: 95 parts of nickel powder, 30 parts of powder, 13 parts of organic carrier, and 6 parts of composite nanomaterial;
[0077] The preparation method of nickel slurry is as follows: preheat the ingredients of the organic carrier in a water bath at 93°C to dissolve the ethyl cellulose into a uniform solution, then add nickel powder, powder and composite nanomaterials into the organic carrier and stir, then grind with a three-roll grinder until the slurry particle size is less than 10μm, and then filter through a 300-mesh nylon mesh.
[0078] The preparation method of the composite nanomaterial is as follows:
[0079] 1) Dissolve 5 g of nickel nitrate in 400 mL of deionized water, add 1.8 g of sodium oxalate and 2.0 g of hexamethylenetetramine, react at room temperature for 6 h, centrifuge, repeatedly wash with ethanol and deionized water, and dry to obtain a nanorod precursor;
[0080] 2) placing the nanorod precursor in a tube furnace, introducing nitrogen, heating to 380°C at 3°C / min, and maintaining for 6 hours, after naturally cooling to room temperature, placing the obtained product and sodium hypophosphite in a mass ratio of 1:13 in a tube furnace, heating to 320°C at 3°C / min, and maintaining for 3 hours, after naturally cooling to room temperature, taking out, washing by centrifugation, and drying to obtain porous nanorods;
[0081] 3) dispersing titanium dioxide nanowires in deionized water to obtain a dispersion with a solid content of 3 wt%, then placing the porous nanorods in a vacuum impregnation container, evacuating to 80 Pa, and then injecting the dispersion into a vacuum impregnation tank at a solid-liquid ratio of 1 g: 20 mL, and maintaining it for 50 min under 200 W ultrasonic action. After the treatment is completed, the product is taken out, centrifuged, washed and dried to obtain a porous nanomaterial;
[0082] 4) The porous nanomaterial is ultrasonically cleaned with acetone, distilled water and ethanol for 50 minutes respectively, and then dried after cleaning to obtain a pretreated porous nanomaterial;
[0083] 5) Dissolve 7 g of cobalt nitrate hexahydrate in 180 mL of a mixed solution of N,N-dimethylformamide and methanol in a volume ratio of 1:3, stir thoroughly, add 13 g of the pretreated porous nanomaterial, and then put them into a reactor together, react at 126° C. for 10 h, cool to room temperature after the reaction is completed, rinse, dry, and then bake for later use;
[0084] 6) The above-mentioned spare product is placed in a tubular furnace, and the temperature is raised to 750°C at 7°C / min in a nitrogen atmosphere, and kept warm for 120 minutes. After cooling to room temperature, the obtained product is reacted with 0.17 mol of thioacetamide at 110°C for 5 hours. After cooling, washing and drying, a composite nanomaterial can be obtained.
[0085] Comparative Example 1: This comparative example is basically the same as Example 1, except that it does not contain composite nanomaterials.
[0086] Comparative Example 2: This comparative example is basically the same as Example 1, except that in the preparation of the composite nanomaterial, steps 1)-2) are omitted.
[0087] Comparative Example 3: This comparative example is basically the same as Example 1, except that step 3) is omitted in the preparation of the composite nanomaterial.
[0088] Comparative Example 4: This comparative example is basically the same as Example 1, except that step 4) is omitted in the preparation of the composite nanomaterial.
[0089] Comparative Example 5: This comparative example is basically the same as Example 1, except that in the preparation of the composite nanomaterial, steps 5)-6) are omitted.
[0090] Test experiment:
[0091] According to the methods provided in Examples 1-3 and Comparative Examples 1-5, nickel paste was printed on a 15mm×20mm×6mm ceramic substrate, dried at 100°C for 10 minutes, and then sintered in an air atmosphere at 600°C for 90 minutes. Test samples were prepared and tested, and the results are shown in Table 1.
[0092] Table 1
[0093] Example 1 Example 2 Example 3 Comparative Example 1 Adhesion / kg 9.6 9.8 9.5 3.7 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Adhesion / kg 5.2 5.8 7.1 6.3
[0094] It can be seen from Table 1 that the nickel paste in the present invention has a strong adhesion to the ceramic substrate, can be firmly attached to the ceramic substrate, has a stable structure, and is not easy to fall off.
[0095] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a Ni electrode strontium titanate ring varistor, characterized in that: The specific steps include: 1) using a servo molding machine to dry-press strontium titanate powder into strontium titanate annular varistor green ceramic sheets; 2) debinding and pre-firing the green ceramic sheet from step 1) at 1000-1200° C.; 3) sintering the green ceramic sheet pre-fired in step 2) in a reducing atmosphere of a mixed gas composed of equal volumes of nitrogen and hydrogen to form a ceramic substrate; 4) subjecting the ceramic substrate of step 3) to an oxidation heat treatment at 800-1000° C. to form an oxide film on the surface; 5) The ceramic sheet of step 4) is screen-printed with a first layer of nickel paste and dried at a temperature of 100-200° C., and then a second layer of silver paste is screen-printed and dried at a temperature of 100-200° C., and then fired in an air atmosphere of 600-800° C.
2. The method for preparing the Ni electrode strontium titanate ring varistor according to claim 1, characterized in that: The nickel paste is made of the following raw materials in parts by weight: 70-95 parts of nickel powder, 5-30 parts of powder, 8-13 parts of organic carrier, and 2-6 parts of composite nanomaterial; The nickel slurry is prepared by preheating the ingredients of the organic carrier in a water bath at 90-93° C. to form a uniform solution, adding nickel powder, powder and composite nanomaterials into the organic carrier and stirring, then grinding with a three-roll grinder until the slurry has a particle size of less than 10 μm, and then filtering with a 300-mesh nylon net.
3. The method for preparing the Ni electrode strontium titanate ring varistor according to claim 2, characterized in that: The powder material includes one or more of glass powder, silicate, silicon dioxide, boron trioxide, bismuth trioxide, and boron powder; The organic carrier is composed of ethyl cellulose, pinene alcohol, dibutyl phthalate and oleic acid mixed in a mass ratio of (10-18): (30-50): (38-42): (0.5-1.2).
4. The method for preparing the Ni electrode strontium titanate ring varistor according to claim 2, characterized in that: The preparation method of the composite nano material is as follows: 1) The porous nanomaterial is ultrasonically cleaned with acetone, distilled water and ethanol for 30-50 minutes respectively, and then dried to obtain a pretreated porous nanomaterial; 2) dissolving cobalt nitrate hexahydrate in the mixed solution, stirring thoroughly, adding the pretreated porous nanomaterial therein, and then placing them together in a reaction kettle, reacting at 120-126° C. for 5-10 hours, cooling to room temperature after the reaction is completed, rinsing, drying, and then drying for standby use; 3) placing the above-mentioned spare product in a tubular furnace, heating it to 700-750° C. in a nitrogen atmosphere, and keeping it warm for 90-120 min. After cooling to room temperature, reacting the obtained product with a sufficient amount of thioacetamide at 100-110° C. for 3-5 h. After cooling, washing and drying, a composite nanomaterial can be obtained.
5. The method for preparing the Ni electrode strontium titanate ring varistor according to claim 4, characterized in that: The usage ratio of the cobalt nitrate hexahydrate, the mixed solution, and the pretreated porous nanomaterial is (3-7) g: (120-180) mL: (5-13) g; The mixed solution is composed of N,N-dimethylformamide and methanol in a volume ratio of 1:(2-3).
6. The method for preparing the Ni electrode strontium titanate ring varistor according to claim 4, characterized in that: The heating rate is 5-7°C / min.
7. The method for preparing the Ni electrode strontium titanate ring varistor according to claim 4, characterized in that: The preparation method of the porous nanomaterial is as follows: 1) dissolving nickel nitrate in deionized water, adding sodium oxalate and hexamethylenetetramine, reacting at room temperature for 4-6 hours, centrifuging, repeatedly washing with ethanol and deionized water, and drying to obtain a nanorod precursor; 2) placing the nanorod precursor in a tube furnace, introducing nitrogen, heating to 350-380°C, and maintaining for 4-6 hours, after naturally cooling to room temperature, placing the obtained product and sodium hypophosphite in a mass ratio of 1:(10-13) in a tube furnace, heating to 300-320°C, and maintaining for 2-3 hours, after naturally cooling to room temperature, taking out, washing by centrifugation, and drying to obtain porous nanorods; 3) Dispersing titanium dioxide nanowires in deionized water to obtain a dispersion, then placing the porous nanorods in a vacuum impregnation container, evacuating to 50-80 Pa, and then injecting the dispersion into a vacuum impregnation tank at a solid-liquid ratio of 1 g: (10-20) mL, and maintaining it for 30-50 minutes under ultrasonic treatment. After the treatment is completed, the product is taken out, centrifuged, washed and dried to obtain a porous nanomaterial.
8. The method for preparing the Ni electrode strontium titanate ring varistor according to claim 7, characterized in that: The usage ratio of the nickel nitrate, deionized water, sodium oxalate and hexamethylenetetramine is (2-5) g: (260-400) mL: (1.3-1.8) g: (1.4-2.0) g.
9. The method for preparing the Ni electrode strontium titanate ring varistor according to claim 7, characterized in that: The heating rate is 1-3°C / min.
10. The method for preparing the Ni electrode strontium titanate ring varistor according to claim 7, characterized in that: The solid content of the dispersion is 1-3 wt %; The power of the ultrasonic action is 150-200W.
Citation Information
Patent Citations
An environmentally friendly silver paste for varistors and its preparation method
CN102262919A
Annular voltage-sensitive resistor and preparation method thereof
CN104134501A
Bismuth-doped copper electrode of strontium titanate annular piezoresistor and preparation method of bismuth-doped copper electrode
CN112768163A
Ohmic contact layer, strontium titanate varistor electrode and preparation methods of ohmic contact layer and strontium titanate varistor electrode
CN118053638A
Copper electrode strontium titanate annular piezoresistor and method for making same
CN1629986A